Elevated Preoperative Serum CA19-9 Levels in Patients with Hepatocellular Carcinoma Is Associated with Poor Prognosis after Resection - Yu-Ling Chen; Chien-Hung Chen; Rey-Heng Hu; Ming-Chih Ho; Yung-Ming Jeng (The Scientific World Journal)
Serum levels of the tumor marker CA19-9 have been reported to be elevated in patients with hepatocellular carcinoma (HCC), but its clinicopathologic significance is still unknown. A cohort of 304 patients undergoing surgical resection for HCC and having preoperative CA19-9 data was enrolled in this study. Serum CA19-9 levels were correlated with clinicopathologic factors. Univariate and multivariate analyses were performed to determine the predictors of patient survival. On receiver operating characteristic curve analysis, the cut off value of CA19-9 was determined to be 27 U/mL. One hundred and six patients had preoperative CA19-9 values >27 U/mL. High serum CA19-9 levels did not correlate with patient age, sex, viral status, α-fetoprotein level, tumor size, tumor grade, tumor stage, multiplicity, and vascular invasion. Patients with elevated preoperative CA19-9 levels had lower 10-year survival than those without CA19-9 elevation. Multivariate analysis revealed that CA19-9 level, tumor grade, and tumor size are independent prognostic factors for long-term survival. In conclusion, a preoperative CA19-9 value >27 U/mL is associated with poor prognosis after resection for HCC.